(3MLjI GdChQGb GdQSejI hGdYQajI hWQb GdWYf YdjgGs - (3eMeO CMeO(B, (3YGHOjfs ((3GdEScfOQjI(B:s (3GdecJH GdYQHj GdMOjK(B,s, 2001)
(3GdUjZ GdbGfhfjI GdNGUI HGdEOYGA HGdJRhjQ, UjZI CNQ ddeGOI (B390 (3GKHGJ , UjZI GYdGf ThGgO GdJRhjQs
Keywords: (3GdChQGb GdQSejIs; (3GdJRhjQs